Philip P. answered • 07/30/14

Tutor

5.0
(472)
Effective and Patient Math Tutor

Let

**m**and**n**be the two numbers. We have two unknowns (m and n) so we need two equations to solve for m and n:m*n = 891 [Product of the two numbers is 891]

m-n = 6 [Difference of the two numbers is 6]

From the second equation, m = 6+n. Now let's substitute 6+n in place of m in the first equation:

m*n = 891

(6+n)*n = 891 [Substituted 6+n in place of m]

6n + n

^{2}= 891n

^{2}+ 6n - 891 = 0Factors to:

(n+33)(n-27) = 0

**n = -33, 27**Solve for m:

m = 6 + n

m= 6 + (-33) = -27

m= 6 + (27) = 33

**There are two solution sets, (m,n) = (-27, -33) and (33,27)**

**CHEC**

**K**

**:**

m*n=891

(-27)*(-33) = 891

891 = 891

(33)*(27) = 891

891 = 891

m-n = 6

(-27)-(-33) = 6

-27 + 33 = 6

6 = 6

33 - 27 = 6

6=6